2018
DOI: 10.1016/j.bjps.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Adults with 22q11.2 deletion syndrome have a different velopharyngeal anatomy with predisposition to velopharyngeal insufficiency

Abstract: Compared with healthy controls, adults with 22q11.2 DS showed a different velopharyngeal anatomy, which will make these individuals more prone to VPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Although only 1 of 6 patients with van der Woude syndrome developed VPI, all of our patients with 22q11.2 deletion syndrome developed VPI. Differences in palate length, levator veli palatini insertion, hypoplastic muscle, and airway structure have been proposed to predispose patients with 22q11.2 deletions to VPI (Sweeney et al, 2015; Filip et al, 2018). All 5 of our patients with Stickler syndrome presented with features of PRS, and 3 of these developed VPI.…”
Section: Discussionmentioning
confidence: 99%
“…Although only 1 of 6 patients with van der Woude syndrome developed VPI, all of our patients with 22q11.2 deletion syndrome developed VPI. Differences in palate length, levator veli palatini insertion, hypoplastic muscle, and airway structure have been proposed to predispose patients with 22q11.2 deletions to VPI (Sweeney et al, 2015; Filip et al, 2018). All 5 of our patients with Stickler syndrome presented with features of PRS, and 3 of these developed VPI.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with 22q11.2DS, imaging studies that included radiographs and magnetic resonance imaging (MRI) have reported the velum to be short, thin, and hypoplastic. 69 The most commonly reported pharyngeal abnormality is a deep pharynx, resulting in an increased velopharyngeal ratio, which is calculated as velar length divided by pharyngeal depth. 6…”
Section: Introductionmentioning
confidence: 99%
“…In individuals with 22q11.2DS, imaging studies that included radiographs and magnetic resonance imaging (MRI) have reported the velum to be short, thin, and hypoplastic. [6][7][8][9] The most commonly reported pharyngeal abnormality is a deep pharynx, resulting in an increased velopharyngeal ratio, which is calculated as velar length divided by pharyngeal depth. 6 The levator veli palatini (levator) muscle is the primary muscle responsible for soft palate elevation and velopharyngeal closure during oral speech sound production.…”
Section: Introductionmentioning
confidence: 99%
“…Such visualisation provides important information that aids patient management decision-making. In addition, MRI is used to investigate the anatomical reasons why some patient groups are more predisposed to speech problems [13] , [14] , [15] , [16] .
Fig.
…”
Section: Introductionmentioning
confidence: 99%